Prevalence of Sexual Dysfunction in People With Systemic Sclerosis and the Associated Risk Factors: A Systematic Review - Rui Gao, MD; Pingying Qing, MD, PhD; Xiaochi Sun, MD; Xun Zeng, MD, PhD; Xiao Hu, MD; Sirui Zhang, MD; Yihong Yang, MD, PhD; Lang Qin, MD, PhD (Sexual Medicine, 2021)
Introduction: The association between systemic sclerosis (SSc) and sexual dysfunction was controversial. Aim: To explore the impacts of SSc on sexual function, the prevalence of sexual dysfunction in patients with SSc and associated risk factors. Methods: A systematic review of all published studies was performed. Studies exploring the association between SSc and sexual function were retrieved from PubMed, Web of Science, and EBSCO. All retrieved papers were selected according to the inclusion and exclusion criteria. Main Outcome Measure: The impacts of SSc on sexual function, the prevalence of sexual dysfunction in males and females with SSc and associated risk factors. Results: A total 12 studies were included in this study. The prevalence of sexual dysfunction in SSc males and SSc females were 76.9–81.4% and 46.7–86.6%, respectively. But the direct impacts of SSc on sexual function were controversial. EULAR SSc activity score ≥3, the number of complications ≥2, and the presence of anticardiolipin antibody and anti U1 ribonucleoprotein antibody in males and resistive index (RI) and the systolic/diastolic (S/D) ratio of clitoral blood in females have potential to be SSc-specific risk factors for sexual dysfunction. Clinical Implications: Clinicians need to pay more attention to the impacts of SSc on sexual function of patients especially in those with risk factors. Strengths & Limitations: Systematically explored the prevalence of sexual dysfunction in SSc males and females, and the risk factors of sexual dysfunction for SSc were explored innovatively. However, there were some limitations in included studies prevented exploring the impacts of SSc on sexual function deeply. Conclusion: Sexual dysfunction may be an important symptom of SSc, many risk factors may be associated with sexual dysfunction in males and females with SSc.Gao R, Qing P, Sun X, et al. Prevalence of Sexual Dysfunction in People With Systemic Sclerosis and the Associated Risk Factors: A Systematic Review. Sex Med 2021;9:100392.